2021
DOI: 10.3390/su13169345
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of the Artisanal and Small-Scale Gold Mining in Northeast Antioquia-Colombia

Abstract: The aim of this work is to explain the concepts of sustainability with respect to small artisanal gold mining. For this, a qualitative approach with a descriptive scope was used, for which the bibliographic review technique was conducted. In this sense, articles, theses, books and institutional documents, and any contribution related to the research topic were taken into consideration. Likewise, this documentation contributed to the delimiting aspects that allowed a contrast between the proposed definitions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The topic of sustainable mining in developing countries has generated interest amongst academics for many years, leading to research in various aspects of the subject by a variety of experts and institutions [22]. Porritt defined sustainability as the capacity of continuity in the long-term future and as the ultimate goal and desired destination of all species [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The topic of sustainable mining in developing countries has generated interest amongst academics for many years, leading to research in various aspects of the subject by a variety of experts and institutions [22]. Porritt defined sustainability as the capacity of continuity in the long-term future and as the ultimate goal and desired destination of all species [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning gold mining, particular attention should be given to illegal and informal gold mining, which is regarded as a worldwide challenge [98] for mining and socioenvironmental regulatory frameworks [99]. Focusing on the analysis of illegal gold mining related data, the authors of [96] suggested that the central problem in FG is the information marginalization and the qualification of the data, which is never raw and is accentuated by the difficulties in accessing to the field.…”
Section: Data Availability: a Specific Focus On Illegal Gold Miningmentioning
confidence: 99%
“…Nevertheless, sustainable thinking within the mining sector could be further improved through the integration of existing cross-disciplinary frameworks. This is especially urgent in the informal and illegal sectors, which are at the crossroad between subsistence and where sustainability performances do not depend on "corporation requirements" [99]. Such frameworks should consider both the diversity and functionality of geo-resources, as well as the different range of needs they might fulfill and the socio-ecological vulnerability of their location.…”
Section: Sustainability and Georesources: Toward Cross-disciplinary F...mentioning
confidence: 99%
“…Without training and capital, the governments of developing countries are formalizing only the pollution as even those artisanal miners with legal mineral titles rarely adopt cleaner practices (Veiga & Marshall, 2019). Restrepo and Mendoza (2021) highlighted the cultural aspect of the artisanal miners in Colombia where the bare subsistence and low economic situation are the main difficulties to allow technical improvements to reach cleaner gold produ ction, particularly when dealing with mercury and cyanide usage. Artisanal miners amalgamate free particles of gold from gravity concentrates or, when the ore has high gold grades as in primary ones, they simply mix mercury with the whole ore in grinding systems, or the ground ore goes over copper plates covered with mercury (amalgamating plates) that captures the liberated gold grains (Spiegel, 2009;Zolnikov & Ortiz, 2018).…”
Section: Introductionmentioning
confidence: 99%